Current Account and Precautionary Savings for Exporters of Exhaustible Resources - Bems, Rudolfs; de Carvalho Filho, Irineu (Washington, D.C. : International Monetary Fund, 2009)
Exporters of exhaustible resources have historically exhibited higher income volatility than other economies, suggesting a heightened role for precautionary savings. This paper uses a parameterized small open economy model to quantify the role of precautionary savings in economies with exhaustible resources, when the only source of uncertainty is the price of the exhaustible resource. Results show that the precautionary motive can generate sizable external sector savings. When aggregated over the sample countries, precautionary savings in 2006 add up to 3.2 percent of GDP. The quantitative importance of the precautionary motive varies considerably across the sample countries and is driven primarily by the weight of exhaustible resource revenues in future income. The parameterized model fares well at capturing current account balances in both cross-section and time-series data.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet